Design and analysis of hybrid filters for harmonic reduction in three-phase nonlinear rectifier loads - Yulianta Siregar; Daniel Julian Sinaga; Nur Nabila Mohamed; Dedet Candra Riawan; Muldi Yuhendri (Bulletin of Electrical Engineering and Informatics, 2026)
Rectifiers are included in the non-linear load category and can create resonance in a distribution network, which can be called harmonics. In a distribution network, rectifiers (non-linear loads) distort voltage and current harmonics, resulting in power losses and reduced power quality in the network. Harmonics in the distribution power grid cannot be eliminated, but can be reduced to values that can still be tolerated and evaluated until they are by the IEEE 519-2014 Standard. This research discusses reducing harmonic values in distribution networks designed in a simulation to implement a combination (hybrid) of series active and passive filters of the high pass and high pass type-C types. The results of research using the installation of high pass filters, type C filters, series active filters, hybrid-1 filters, and hybrid-2 filters, respectively, for each current total harmonic distortion (THD) value are 15.93%, 16.15%, 8.51%, 0.27%, and 0.25% where the current THD value when using the two hybrid filters is below the specified standard limit, namely 5%. By installing a hybrid filter, the harmonic value in each feeder is much better than installing a single series active filter, a high pass filter, and a type-C filter.